Technological-Based Application in Writing Instruction: A Model of Project-Based Learning - Amalia, Ila; Marzuki, Abdul Gafur; Anita, Anita; Rahmawati, Eulis; Ulfah, Ulfah (Universitas Cokroaminoto Palopo, 2024)
This study aimed to describe the implementation of technologically based applications for teaching writing. We used Storyjumper, a digital writing tool, as a technological application to complete a writing assignment. We used a case study method to understand the students' involvement in utilizing digital tools for writing assignments within a project-based learning framework. This study also aimed to describe the students’ perceptions of using the digital writing tool Storyjumper in writing activities. We collected the data using a 5-point Likert scale questionnaire and an observation technique, adhering to Stoller's (2006) project-based learning steps. The findings revealed that we could categorize the project-based model for teaching writing using a technological application into three stages: the planning stage, the implementation stage, and the reporting stage. We then expanded these steps into more specific stages. Meanwhile, the results of the questionnaire data analysis showed that students had positive attitudes toward using Storyjumper in writing activities. Storyjumper proved to be an engaging tool for writing activities, effectively enhancing students' writing efficiency and performance while fostering flexibility in terms of time and place to write.